Population fluctuations of Rhyacionia buoliana in a Pinus radiata plantation of the X Region - Ide, Sandra E.; Lanfranco, Dolly M. (Bosque (Valdivia), 1994)
Population density of the European pine shoot moth, Rhyacionia buoliana (Schiff), on Pinus radiata D. Don plantations, established in 1986 in two different sites are analyzed, monitoring permanent plots during six years. Survival and mortality of the moth were also determined. Changes in density reveal annual increments and significant differences between sites. The influence of denso independent factors and the absence of natural enemies as regulators of the population leves are discussed. The survival increase trough time is interpreted as a consequence of the good adaptation of the species to different site conditions. The highest mortality rate occurred during the exposed periods of the moth's life cycle and principally at the early larvae stage mostly due to dehydration, resination and predation.